DESIGN OF “KENSEMAX BUSINESS CENTER” MULTI-STORY COMMERCIAL BUILDING IN SAN-FRANCISCO, USA - Yessengeldin, Ali; Zhunisbek, Amirzhan; Bauyrzhanov, Arulan; Zhumabek, Baryskhan; Kakabay, Bernar; Mukhamedkhan, Kuanysh; Maulembayev, Serikbolsyn (Nazarbayev University School of Engineering and Digital Sciences, 2024)
The main objective of this project is to design a multi-story commercial building located in San Francisco, California, USA. The address of the construction site is located at 2555 Irving St., Sunset District of San Francisco city. This project aims at increasing the commercial activity in the neighborhood by providing office spaces for companies of various sizes. The design is done by implementing previously obtained knowledge from courses in different disciplines of civil engineering, including architectural, structural, geotechnical, environmental design, and construction management. The design of the structure and foundations was done according to the local building codes, mainly ASCE-7 by American Society of Civil Engineers and International Building Code (IBC). The design process involved performing hand calculations the results of which were then compared with the simulation results of software such as SAP2000, GEO5, and PLAXIS 3D. The architectural and structural parts of the project focus on designing a structure that will be able to withstand the conditions from the surrounding environment, including seismic activity, corrosion, dead, live, and wind loads. The geotechnical part involves designing a proper foundation that will act as a support for transferring the structural loads from the building to the soil. Environmental design focuses on developing a strategy that will help to efficiently manage the waste produced by the daily activities of customers that rent the office spaces of the building. The purpose of construction management is to create a strategy for a more efficient allocation of resources, organizing the construction process into smaller tasks, reviewing various risks that may occur during the construction project.
Keywords: Type of access: Open access; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture